1997
DOI: 10.1101/gr.7.5.471
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency of Microsatellites in the Avian Genome

Abstract: A better insight into the occurrence of microsatellites in a range of taxa may help to understand the evolution of simple repeats. Previous studies have found the relative abundance of several repeat motifs to differ among mammals, invertebrates, and plants. Absolute numbers of microsatellites also tend to correlate positively with genome size. We analyzed the occurrence, frequency, and distribution of microsatellites in birds, a taxon with one of the smallest known genome sizes among vertebrates. Dot-blot hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
1
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(169 citation statements)
references
References 46 publications
(68 reference statements)
9
154
1
5
Order By: Relevance
“…Thus, genome size in bats is controlled by broad-based regulatory forces that maintain low copy numbers of repetitive DNA families (Van Den Bussche et al 1995). Microsatellites are even rarer in avian genomes (Primmer et al 1997), and repetitive DNA in general appears scarce in birds (Eden et al 1978;Epplen et al 1978;Wagenmann et al 1981;Venturini et al 1987;Bloom et al 1993). This general fact about bird genomes is even displayed in miniature within the major histocompatibility complex of chicken (Parham 1999).…”
Section: Genomic Baggage: Lost or Never Loaded?mentioning
confidence: 99%
“…Thus, genome size in bats is controlled by broad-based regulatory forces that maintain low copy numbers of repetitive DNA families (Van Den Bussche et al 1995). Microsatellites are even rarer in avian genomes (Primmer et al 1997), and repetitive DNA in general appears scarce in birds (Eden et al 1978;Epplen et al 1978;Wagenmann et al 1981;Venturini et al 1987;Bloom et al 1993). This general fact about bird genomes is even displayed in miniature within the major histocompatibility complex of chicken (Parham 1999).…”
Section: Genomic Baggage: Lost or Never Loaded?mentioning
confidence: 99%
“…Here, only the positive clones for the PCR screening were sequenced (16 for S. hirundinacea and 8 for R. niger) and none of them were found to be true microsatellite sequences. The percentage of positive clones using traditional methods of microsatellite isolation (non-enriched libraries) has been found to be lower in birds (0.46%), compared to other taxa, such as mammals (1.67%) and fish (3.1%; Primmer et al, 1997;Zane et al, 2002). Even considering that in our study a relatively low number of clones were screened (about 2000), our results suggested that the frequency of microsatellites in S. hirundinacea and R. niger may be than for other species of birds studied to date.…”
Section: Resultsmentioning
confidence: 98%
“…It is known that the abundance of microsatellites across the taxa varies by orders of magnitude (Nève and Meglécz, 2000), and in some groups, such as birds, their frequency is relatively low (Primmer et al, 1997;Neff and Gross, 2001). In addition, major difficulties in the isolation of these markers have been reported for groups such as leptidoptera (Saccheri and Bruford, 1993), birds (Beaumont and Bruford, 1999) and some plants (Squirrell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, AFLP markers can be expected to provide a better coverage of microchromosomes than microsatellites. Indeed, as a result of the GC-rich and gene-dense nature of microchromosomes [22,38] together with the type of polymorphism revealed by each technique, microsatellites are underrepresented on these chromosomes [30], whereas the AFLP technique, using TaqI or other enzymes, such as MspI or HinP1I [17] with GC-rich recognition sites, could better target these zones.…”
Section: Discussionmentioning
confidence: 99%
“…[6,34]), and as a model for a variety of studies in embryonic development, genetics, In linkage studies, microsatellite markers are currently used because they are highly polymorphic and codominantly inherited. However, they occur at about a 5-7-fold lower frequency in avian genomes than in mammals [30] and are thought to be biased in their distribution [30,38]. In addition, cross-species microsatellite amplification in birds is successful only at a low rate.…”
Section: Introductionmentioning
confidence: 99%